Hepatoprotective activities of Antrodia camphorata and its triterpenoid compounds against CCl4-induced liver injury in mice. (12th July 2017) - Li, Zi-wei; Kuang, Yi; Tang, Shu-nan; Li, Kai; Huang, Yun; Qiao, Xue; Yu, Si-wang; Tzeng, Yew-min; Lo, Jen-Yu; Ye, Min
Abstract: Ethnopharmacology relevance: Antrodia camphorata (AC) is a rare and precious fungus indigenous to Taiwan used as a traditional medicine for the treatment of liver injury. Triterpenoids are the major bioactive constituents of A. camphorata and have been reported to possess hepatoprotective activities. To meet the increasing demand, artificial cultivation techniques have been developed. Aim of the study: This study aims to evaluate the hepatoprotective activities of AC samples derived from different cultivation techniques and to dissect the main active triterpenoid compounds. Materials and methods: The ethanol extracts of five batches of AC samples, including wild growing fruiting bodies, cutting wood culture fruiting bodies, dish cultures, cutting wood culture mycelia, and submerged fermentation mycelia were orally administered (50 mg/kg or 200 mg/kg) to ICR mice for 7 days. On the last day, CCl4 (0.2%, 7 mL/kg, i.p.) was used to induce liver injury, and the activities of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were determined 24 h after the injection. Moreover, a HepG2 cell model treated with CCl4 (0.35%) was used to screen the protective activities of 29 AC triterpenoids. After incubation for 6 h, viabilities of the cells were tested using MTS assay. The in vivo hepatoprotective activities of antcin B and antcin K were further studied on the mice model by ALT and AST tests and histopathologic examinations. To elucidate the mechanisms, the mRNA levels of iNOS, COX2, TNF-α and IL-1β, and the protein levels of NF-κB (p65/p-p65), iNOS and COX2 in liver tissues were determined. Results: The wild growing or cutting wood culture fruiting bodies, and the dish cultures of AC showed more potent activities than the mycelia ( P <0.001). At 20 μM, 16 of 29 triterpenoids showed significant protective activities, increasing HepG2 cell viability from 46% of the CCl4 group to >90%. Antcin B and antcin K could dose-dependently (10 or 50 mg/kg, 7 days, i.g.) decrease the serum levels of ALT and AST, and decrease the incidence of liver necrosis. The effects of 50 mg/kg of antcin K or antcin B were almost identical to those of 100 mg/kg silymarin. Furthermore, qRT-PCR and Western blotting analyses revealed they could down-regulate IL-1β, TNF-α, iNOS, COX-2 and NF- κ B in liver tissues at both transcriptional and translational levels. Conclusion: The results indicate that cultivation techniques remarkably affect the hepatoprotective activities of AC. Antcin K and antcin B are the major hepatoprotective compounds of A. camphorata, and the mechanism is related with anti-inflammation. Given its high natural abundance and good oral absorption, antcin K could be a promising drug candidate for liver injury. Graphical abstract: